Distribution of physicochemical in the coastal waters of Sembilang National Park, Banyuasin Regency, South Sumatra, Indonesia - Fitri Agustriani; Fauziyah Fauziyah; Ellis Nurjualisti Ningsih; Amanda Astri Pratiwi Febrianti (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2026)
Sembilang National Park (SNP) is a large mangrove area and plays an important role in Indonesia, where it has important economic value, especially fisheries resources, a route for protected types of marine biota, and a potential fishing area. Good water quality conditions can optimize the function of the SNP area as an ecosystem for various existing biological resources. The aimed of study was to analyze the relationship between physical and chemical parameters in the inner and outer zones of the mangrove ecosystem. Data was collected directly in situ such as DO, pH, salinity, nitrate, and phosphate. Analysis of the distribution of physical and chemical water data was using Surfer 9 software. Analysis of the relationship between physical and chemical parameters using Principal Component Analysis (PCA). The results showed that the water quality in SNP was still in good condition for biota growth, however, nitrate and phosphate showed high values at 4.32-6.52 mg/land 0.12-0.19 mg/L. Principal Component Analysis (PCA) showed that the estuary zone was characterized by nitrate and phosphate parameters, while the outer estuary zone was characterized by DO, pH, and salinity parameters. The dynamics of the physicochemical parameters of the waters in the SNP area are generally in good condition, except for nitrate and phosphate, which are indicated to cause eutrophication.